Penilaian Otentik Dalam Konteks Penilaian Karakter - Dianita Rahayu Sukmawati; Roulina Magdalena Siburian; Nur Hidayatil Janah; Ratna Sari Dewi (Jurnal Bintang Pendidikan Indonesia, 2023)
Character education is a process that helps each individual in developing more noble characters, namely honesty, responsibility, tolerance, and others. Character education in schools aims to make students conform to what is expected, when the character of each student is formed very well, then each individual will get used to something that has been instilled from an early age, but it is different when an individual is less directed at character education, then these students will be minimal in the formation of good character. Therefore, character education must continue to be instilled both in the school environment (education), in the family environment, even in the community. In character education there is a character evaluation that can be carried out by the teacher. The evaluation will be an assessment of whether the student is in accordance with the character achieved or vice versa.